Produção e aplicação de ramnolipídios produzidos por Pseudomonas aeruginosa LBI 2A1 - Ceccato, Heloise Dugolin [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The environmental problem related to the contamination of soils and effluents by heavy metals from various activities leads to the development of researches aiming at less impactful ways to remove these metals. Rhamnolipids application produced by Pseudomonas aeruginosa strains shows advantages in this respect, since several researches indicate that this biosurfactant can get better results than commercial surfactants. As the production costs of this bioproduct are high, its applications are often limited to the noblest purposes. Therefore, in order to reduce costs, the present study tested the production of rhamnolipids by Pseudomonas aeruginosa utilizing used waste cooking oil from UNESP Rio Claro’s University Restaurant as a carbon source. The biosurfactant produced was applied to remove heavy metals as lead, copper, nickel and zinc from residual soils of ceramic activity arising from Região dos Lagos (the Lakes Region), in Santa Gertrudes, state of São Paulo. Soil washing experiments were carried out on rotary shakers using rhamnolipids at initial concentrations of 0.5 g/L and 1.0 g/L, as well as cell-free resulting from fermentation, on pH values 8,0 and 9,0. Results were compared to the application of commercial surfactant sodium dodecyl sulfate (SDS). Higher percentages of removal occurred with cell-free broth at pH 8,0, corresponding to 5.505%, 1.268%, 1.245% and 0.843%, respectively for lead, copper, zinc and nickel. The use of cell-free broth has economic advantages, as it is not necessary to perform the rhamnolipid extraction, step encumbering the process. In some cases, removal percentages using SDS were lower than with cell-free broth and rhamnolipids solution, reaching the maximum value of 0.115% for lead, which draws attention to the competitive advantage of biosurfactant instead of SDS, besides environmental advantages. Although the results are favorable, further researches are needed to improve this methodology in...

O problema ambiental relacionado à contaminação de solos e efluentes por metais pesados oriundos de diversas atividades leva ao desenvolvimento de pesquisas visando formas menos impactantes de remoção desses metais. A aplicação de ramnolipídios produzidos por linhagens de Pseudomonas aeruginosa se mostra vantajosa neste aspecto, visto que diversas pesquisas indicam que este biossurfactante pode obter melhores resultados que os surfactantes comerciais. Como os custos de produção deste bioproduto são elevados, suas aplicações são por vezes limitadas a fins mais nobres. Por isso, visando reduzir os custos, o presente trabalho realizou a produção de ramnolipídios por Pseudomonas aeruginosa utilizando-se óleo de fritura usado do Restaurante Universitário da UNESP – Rio Claro como fonte de carbono. O biossurfactante produzido foi aplicado à remoção dos metais pesados chumbo, cobre, níquel e zinco de solos residuais da atividade cerâmica advindos da Região dos Lagos, em Santa Gertrudes - SP. Foram realizados experimentos de lavagem de solo em mesa agitadora, nas concentrações iniciais de 0,5 g/L e 1,0 g/L de ramnolipídios, além do caldo livre de células resultante da fermentação, nos valores de pH 8,0 e 9,0. Os resultados foram comparados à aplicação do surfactante comercial Dodecil Sulfato de Sódio (SDS). As maiores porcentagens de remoção ocorreram com o caldo livre de células em pH 8,0, sendo iguais a 5,505%, 1,268%, 1,245% e 0,843%, respectivamente para chumbo, cobre, zinco e níquel. O uso do caldo apresenta vantagens econômicas, pois não é necessário realizar a extração do ramnolipídio, etapa que onera o processo. As porcentagens de remoção com o SDS foram mais baixas do que as com o caldo e com a solução de ramnolipídios em alguns casos, chegando a seu valor máximo de 0,115% para o chumbo, o que salienta a vantagem competitiva do biossurfactante sobre o surfactante comercial, além das...
Keywords: Resíduos; Pseudomonas aeruginosa; Ceramica - Indústria - Resíduos; Biossurfactantes; Metais pesados; Solos - Poluição; Solos - Remediação